Carbon‐iodide bond activation by cyclometalated Pt (II) complexes bearing tricyclohexylphosphine ligand: A comparative kinetic study and theoretical elucidation. (19th November 2018) - Chamyani, Samira; Shahsavari, Hamid R.; Abedanzadeh, Sedigheh; Golbon Haghighi, Mohsen; Shabani, Sepideh; Notash, Behrouz
Abstract : Cyclometalated Pt (II) complexes [PtMe(C^N)(L)], in which C^N = deprotonated 2, 2′‐bipyridine N ‐oxide (Obpy), 1, deprotonated 2‐phenylpyridine (ppy), 2, deprotonated benzo [h] quinolone (bzq), 3, and L = tricyclohexylphosphine (PCy3 ) were prepared and fully characterized. By treatment of1–3 with excess MeI, the thermodynamically favored Pt (IV) complexes cis ‐[PtMe2 I(C^N)(PCy3 )] (C^N = Obpy, 1a ; ppy, 2a ; and bzq, 3a ) were obtained as the major products in which the incoming methyl and iodine groups adopted cis positions relative to each other. All the complexes were characterized by means of NMR spectroscopy while the absolute configuration of1a was further determined by X‐ray crystal structure analysis. The reaction of methyl iodide with1–3 were kinetically explored using UV–vis spectroscopy. On the basis of the kinetic data together with the time‐resolved NMR investigation, it was established that the oxidative addition reaction occurred through the classical SN 2 attack of Pt (II) center on the MeI reagent. Moreover, comparative kinetic studies demonstrated that the electronic and steric nature of either the cyclometalating ligands or the phosphine ligand influence the rate of reaction. Surprisingly, by extending the oxidative addition reaction time, very stable iodine‐bridged Pt (IV)‐Pt (IV) complexes [Pt2 Me4 (C^N)2 ( μ ‐I)2 ] (C^N = Obpy, 1b ; ppy, 2b ; and bzq, 3b ) were obtained and isolated. In order to find a reasonable explanation for the observation, a DFT (density functional theory) computational analysis was undertaken and it was found that the results were consistent with the experimental findings. Abstract : The kinetico‐mechanistic aspects of the oxidative addition reaction of MeI to a series of cycloplatinated (II) phosphine complexes were investigated.